Penerapan Teknologi Blockchain dalam Akuntansi Syariah - Ahmad Fuadi Tanjung; Patma Wati; Nurlaila Nurlaila (Universitas Muhammadiyah Surabaya, 2023)
AbstractThis research aims to examine the application of blockchain technology, the benefits, advantages, challenges, and disadvantages of this technology. The method used is descriptive qualitative using literature study. The data in this study used secondary data obtained from various sources such as journals, books, reports and other documents. This research shows that the application of blockchain technology in the Islamic accounting industry provides benefits such as high data security and transparency of financial information for business people and potential investors.Keywords: Implementation, Blockchain Technology, Sharia Accounting